RETRACTED ARTICLE: β-Adrenergic receptor structure and function: molecular insights guiding the development of novel therapeutic strategies to treat malignancy. (2nd September 2020) - Ghali, Michael G. Z.; Arborelius, Ulf P.; Yaşargil, M. Gazi
Abstract: We, the Editors and Publisher of the Journal of Receptors and Signal Transduction, have retracted the following article and its correction notice: Michael G. Z. Ghali, Ulf P. Arborelius & M. Gazi Yaşargil (2020) β-Adrenergic receptor structure and function: molecular insights guiding the development of novel therapeutic strategies to treat malignancy, Journal of Receptors and Signal Transduction, 40:5, 395-409, DOI: 10.1080/10799893.2020.1759091 None, Correction, 40:5, I-II, DOI: 10.1080/10799893.2020.1782010 Since publication, we were contacted by one of the co-authors who alerted us to the fact that this article was published without their knowledge or consent. We have contacted the corresponding author for an explanation, but we have not received a response. In addition, we were unable to verify that the second co-author had also contributed and consented to the publication of this article. We contacted the institution of the corresponding author, as listed in the affiliation, funding sections, who confirmed that the author is not and has not been affiliated with their institution. As accurately stating authorship and affiliated institution is core to the integrity of published work, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.